Kesadaran Profetik : Upaya Mereduksi Neokolonialisme dalam Pendidikan - Nova Nafisah Zulfa; Muhamad Parhan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Educational neocolonialism is a planned policy of developed countries to maintain their influence over developing countries which is a continuation of past practices. In line with Paulo Freire's ideas in his book "Education of the Oppressed", educational neocolonialism is the new face of "oppression" in the world of education in Indonesia. The aim of this research is to find a grand solution to the problem of this new form of colonialism. This research approach is qualitative with a library study method, namely reviewing books, literature and notes related to the topic raised. The concept of "Prophetic Awareness" presented by Kuntowijoyo (2001) in a book by Abdul Halim Sani (2011) can offer a solution to the above phenomenon, harmony between reason and faith which is manifested through a process of humanization-theocentric, liberation and transcendence, it is hoped that it can restore identity. Indonesian education is based on the divine principle of justice.